Analysis of Singgahan-Tuban Karst Geopark as a Social Science Learning Resource Facility in Outdoor Learning Activities - Prasetya, Sukma Perdana; Sarmini, Sarmini; Zein, Ita Mardiani; Artono, Artono; Sadewo, FX Sri; Mahat, Hanifah (International Journal of Social Learning (IJSL), 2022)
This study aimed to explore the potential of geopark karst as a source of social studies learning in outdoor learning activities. The subjects of the study were 25 social studies teachers. Primary data in the form of direct observation and participation in the field, as well as the results of interviews with several key informants and supporters. Data analysis was obtained through three stages: data reduction, data presentation, and concluding. The following analysis technique uses SWOT analysis which produces a strategy formulation in utilizing the karst potential of the Singgahan Geopark as a source of social studies learning in outdoor learning activities. The most significant potential strength factor is the many variations of population adaptation to karst phenomena in outdoor learning locations, so it is interesting to study from the aspect of social interaction and the environment.